A study of students’ learning perceptions and behaviors in remote STEM programming education - Su, Yu-Sheng; Chang, Ching-Yao; Wang, Cheng-Hsin; Lai, Chin-Feng (Frontiers in Psychology, 2022)
In recent years, STEM education has developed students' fundamental subject knowledge. Students can integrate STEM cross-domain knowledge. Universities emphasize innovative thinking, practice and application, problem-solving, and teamwork to nurture students to learn STEM cross-domain knowledge development in remote STEM program education. When students study online STEM programs, they encounter unanswered questions and give up solving them. Therefore, this study proposes a problem-based learning approach with an online programming system integrated into an online STEM programming course. To solve the past programming assignments, the assignments will be simplified, decomposed, and reorganized. The teacher guides the students to understand the STEM programming problems and teaches them to use appropriate problem-solving skills to motivate them to complete the STEM programming assignments. The experiment was conducted with students in an online STEM programming course at a university in northern Taiwan. In the experimental activities, we used a problem-based learning approach for the online STEM programming activity. The problem-based learning method can be divided into four steps, namely stating the problem, understanding the problem, developing a solution plan, executing the plan, reflecting, and debugging. This study used a problem-based learning approach and an online programming system integrated into a STEM programming curriculum to explore the differences in students' perceptions of STEM learning, learning outcomes, and learning behaviors. The experimental results found that there was a significant difference between students' prior knowledge and learning outcomes. In the analysis of STEM learning perceptions, we found that there were significant differences in students' responses to the questionnaire on the STEM learning perceptions for each dimension. In the analysis of students' behaviors in answering STEM programming assignments, it was found that some students had the habit of taking notes. This helps students to easily associate and integrate STEM cross-domain knowledge with what they have learned in the online course and enhances their ability to implement STEM programs.